Study on Mechanical and Thermal Behaviour of Rotor Brake Using Computer Aided Engineering Software - Yusof, Sarah; Jafferi, Noormaziah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The disc brake system is one of the most essential parts of a moving vehicle since it helps to keep the drivers and passengers safe. A disc brake system is a kind of brake that uses callipers to press pairs of pads against a disc or rotor to create friction. The purpose of this study was to model and simulate disc brakes rotor using computer-aided engineering software, as well as to investigate the impact of mechanical and thermal behaviour on the designated disc brake. The disc brake simulation has be carried out using the finite element method in SolidWorks 2019 with four suggested materials: gray cast iron, titanium alloy, aluminium metal composite (AMC), and stainless steel with two alternative mesh density variations. Thermal distribution, stress, displacement, and strain are the comparisons to be assessed in variation of nodes and materials of disc brake. Each behaviour has its own set of best materials. Aluminium metal composite, has the lowest thermal distribution with value of 230 K for both Proton Saga Standard 1.3 AT and Honda City 1.5L E. Stainless steel has the greatest stress with the value 1000 MPa and 967.2 MPa for Proton Saga and Honda City respectively. In term of displacement, aluminium metal composite has highest displacement compared to other materials with value 0.5769 mm for Proton Saga and 0.5795 mm for Honda City. Aluminium metal composite is also has highest strain with the value of 4.238x10-3 and 3.938x10-3 for Proton Saga and Honda City respectively.